The selfish gene - Dawkins, Richard (Oxford University Press, 1989)
This million-copy bestseller is universally acclaimed and translated into over twenty languages. "The sort of popular science writing that makes the reader feel like a genius." - "New York Times." "This important book could hardly be more exciting." - "The Economist." "Learned, witty, and very well written...exhilaratingly good." - "Spectator." "The reader will come away with a clear understanding of kin selection, evolutionary stable strategies, and evolutionary theories of animal behaviour. This is a considerable achievement." - "THES." "The exciting theories and their wide implications are explained with clarity, wit and enthusiasm." - Peter Parker, "Sunday Times." "This book should be read, can be read, by almost everyone. It describes with great skill a new face of the theory of evolution." W. D. Hamilton, "Science." "The presentations are remarkable for their clarity and simplicity, intelligible to any schoolchild, yet so little condescending as to be a pleasure to the professional." - "American Scientist."